2022
DOI: 10.3389/fnut.2022.867150
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, Epigenetics, and Major Depressive Disorder: Understanding the Connection

Abstract: Major depressive disorder (MDD) is a complex, multifactorial disorder of rising prevalence and incidence worldwide. Nearly, 280 million of people suffer from this leading cause of disability in the world. Moreover, patients with this condition are frequently co-affected by essential nutrient deficiency. The typical scene with stress and hustle in developed countries tends to be accompanied by eating disorders implying overnutrition from high-carbohydrates and high-fat diets with low micronutrients intake. In f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 175 publications
1
12
0
Order By: Relevance
“…Rather than being specific for a certain psychiatric diagnosis, butyrate-producing bacteria such as Faecalibacterium and pro-inflammatory bacteria such as Eggerthella were altered in people with MDD, bipolar disorder, schizophrenia and anxiety disorders in a transdiagnostic pattern [14 ▪▪ ]. This also corresponds to the earlier finding that genetic influences on psychiatric disorders [18] transcend diagnostic limits [19], which may also be the case for the epigenetic influences from the gut microbiome [20 ▪ ]. The majority of studies reported no significant differences in alpha diversity of individuals with MDD and healthy controls.…”
Section: Gut Microbiome Composition In Depressionsupporting
confidence: 76%
“…Rather than being specific for a certain psychiatric diagnosis, butyrate-producing bacteria such as Faecalibacterium and pro-inflammatory bacteria such as Eggerthella were altered in people with MDD, bipolar disorder, schizophrenia and anxiety disorders in a transdiagnostic pattern [14 ▪▪ ]. This also corresponds to the earlier finding that genetic influences on psychiatric disorders [18] transcend diagnostic limits [19], which may also be the case for the epigenetic influences from the gut microbiome [20 ▪ ]. The majority of studies reported no significant differences in alpha diversity of individuals with MDD and healthy controls.…”
Section: Gut Microbiome Composition In Depressionsupporting
confidence: 76%
“…On the one hand, malnutrition can drive several biological changes that can lead to the onset and progression of MDD. On the other hand, MDD can drive to eating disorders and lifestyle behaviors that may promote malnutrition [ 26 ]. However, there is an important association between malnutrition and MDD that can be observed in these patients.…”
Section: Major Depressive Disorder and Diet: What Is The Relationship?mentioning
confidence: 99%
“…The wellknown herb St. John's Wort, despite being best-selling, the FDA has not given any authorization to use as a nonprescribed or prescription drug for depression due to some safety and efficacy issues (Di Carlo et al, 2001;Ionescu et al, 2022). ω-3 fatty acids and S-adenosylmethionine (SAMe) are used as natural dietary remedies but remain under study due to no proof of safety and effectiveness for daily use (Kasper, 2022;Ortega et al, 2022;Singh et al, 2024). Besides treatment with antidepressant drugs, among other available approaches, following are the common therapies to manage the symptoms of depression: Support: It can be possible by providing practical knowledge and information to the family members of the patient to help the depressive person reduce symptoms, boost self-confidence, reestablish a connection to reality, control urges and negative thoughts, and strengthen coping mechanisms for stressful and difficult situations in life (Gaynor et al, 2003).…”
Section: Introductionmentioning
confidence: 99%